2018
DOI: 10.1016/j.jhep.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Toronto HCC risk index: A validated scoring system to predict 10-year risk of HCC in patients with cirrhosis

Abstract: HCC incidence varies markedly depending on the underlying cause of cirrhosis. Herein, using readily available clinical and laboratory parameters we describe a risk score, THRI, which has a good predictive ability for HCC in patients with cirrhosis, and has been validated in an external cohort. This risk score may help to guide recommendations regarding HCC surveillance among patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
169
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(180 citation statements)
references
References 34 publications
8
169
3
Order By: Relevance
“…Our results also suggest that AFP can be a powerful predictor of HCC when used in combination with other risk factors, even if it is not adequate as a sole screening test. Investigators have recently attempted to develop algorithm-based risk models to estimate HCC risk and target high-risk patient populations for screening[ 26 , 27 , 35 , 50 ]. Many of these models include AFP and other variables described in this study, and have shown early promise, though they have yet to be validated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that AFP can be a powerful predictor of HCC when used in combination with other risk factors, even if it is not adequate as a sole screening test. Investigators have recently attempted to develop algorithm-based risk models to estimate HCC risk and target high-risk patient populations for screening[ 26 , 27 , 35 , 50 ]. Many of these models include AFP and other variables described in this study, and have shown early promise, though they have yet to be validated in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…33 In the large validation cohort included in the CAMD score study, the 3-/5year HCC predictability of PAGE-B was similar to that of CAMD score. 28 Finally, in the validation cohort of mPAGE-B study, the researchers also assessed the predictability of PAGE-B, CU-HCC, GAG-HCC and REACH-B as well as of the Toronto HCC risk index (THRI) score, 40 which was originally introduced to predict HCC development in patients with cirrhosis regardless of aetiology.…”
Section: Independent Validati On Of H CC Ris K Score S In a S Ian Pmentioning
confidence: 99%
“…Our RNN models exhibited an AUROC of 0.759 among all samples and 0.806 among samples from patients with SVR, which is considered very good and compares favorably with other HCC risk prediction models. 6 , 45 , 46 Equally importantly, our models had great calibration and excellent agreement between observed and predicted HCC risk ( Table 3 ).…”
Section: Discussionmentioning
confidence: 70%